2021
DOI: 10.3389/fmed.2021.683211
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chinese Herbal Medicines on Hearing Loss Risk in Rheumatoid Arthritis Patients: Retrospective Claims Analysis

Abstract: Objectives: Patients with rheumatoid arthritis (RA) are at a higher risk of extra-articular manifestations, especially hearing loss (HL). Although Chinese herbal medicines (CHM) are proven safe and effective treatments for inflammatory conditions, the effect of CHM use on HL in RA patients is unknown. This cohort study aims to determine the relationship between CHM use and the subsequent risk of HL among RA patients.Methods: From health insurance claims data in Taiwan, a total of 6,905 persons aged 20–80 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
(42 reference statements)
1
3
0
Order By: Relevance
“…No data available from previous research have shown this relationship, rendering a direct comparison of results impossible. Yet, the findings obtained herein are consistent with earlier research findings on other outcomes and add to the growing body of knowledge on the beneficial effects of CHM for patients with chronic diseases ( Chan and Ng, 2020 ; Li H.-H. et al, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…No data available from previous research have shown this relationship, rendering a direct comparison of results impossible. Yet, the findings obtained herein are consistent with earlier research findings on other outcomes and add to the growing body of knowledge on the beneficial effects of CHM for patients with chronic diseases ( Chan and Ng, 2020 ; Li H.-H. et al, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…From the database, we collected claims data submitted for subjects aged 20–80 years, and they had at least one admission code or three or more outpatient codes for asthma within 365 calendar days between 2000 and 2007 (ICD-9-CM code 493). This algorithm of at least one inpatient visit or three outpatient visits in a 12-months span was often used to define the diseases while using the administrative claims data in from LHID ( Wang Y. et al, 2020 ; Li H.-H. et al, 2021 ). Overall, we enrolled 34,485 cases with new-onset asthma.…”
Section: Methodsmentioning
confidence: 99%
“…Despite a lack of comparable studies, the result added to the body of the literature suggesting the clinical efficacy of CHM for individuals with chronic diseases. 22,23 After stratifying patients by age and gender, we noticed that females benefited more from CHM treatment than males. Numerous surveys focusing on gender differences in health-related knowledge and healthy behaviors found that females are more aware of the importance of self-care than males.…”
Section: Discussionmentioning
confidence: 96%
“…Despite a lack of comparable studies, the result added to the body of the literature suggesting the clinical efficacy of CHM for individuals with chronic diseases. 22 , 23 …”
Section: Discussionmentioning
confidence: 99%
“…The classification of patients with pSS based on diagnostic methods in Eastern medicine is also a difficult task. The mechanism of Jia-Wei-Xiao-Yao-San (JWXYS) in autoimmune disease was observed to increase synaptic plasticity and decrease the levels of inflammatory markers by upregulating the expression of hippocampal brain-derived neurotrophic factor (BDNF) (5)(6)(7). Suan-Zao-Ren-Tang (SZRT) could regulate the gammaaminobutyric acid-ergic(GABA) system in plasma which is crucial in the etiology of psychiatric disorders (8).…”
Section: Introductionmentioning
confidence: 99%